Thrombotic thrombocytopenic purpura: An unusual presentation with intracranial bleed (Indian Journal of Case Reports, 2021)
Thrombotic thrombocytopenic purpura (TTP) is a rare and life-threatening thrombotic microangiopathy characterized by microangiopathic hemolytic anemia, severe thrombocytopenia, and organ ischemia linked to disseminated microvascular platelet-rich thrombi. We present the case of a 44-year-old lady who presented with severe thrombocytopenia and anemia that did not respond to repeated transfusions and steroids. Non-contrast computed tomography scan of the brain revealed an intracranial bleed. Schistocytes were seen on the peripheral blood smear. A provisional diagnosis of TTP was made. Plasmapheresis could not be done due to her deteriorating hemodynamic status. She succumbed to her illness in spite of the best possible efforts. This case highlights the need for keeping a high index of suspicion for TTP as early diagnosis and prompt initiation of plasmapheresis are crucial for preventing death.